Defluvicoccus vanus gen. nov., sp. nov., a novel Gram-negative coccus/coccobacillus in the 'Alphaproteobacteria' from activated sludge - Maszenan, A M; Seviour, R J; Patel, B K C; Janssen, P H; Wanner, J (International journal of systematic and evolutionary microbiology, 2005)
A novel Gram-negative coccus/coccobacillus, strain Ben 114(T), growing in tetrads, clusters or aggregates, was isolated from activated sludge by micromanipulation. 16S rRNA gene sequence analysis revealed that it belonged to the 'Alphaproteobacteria', with no close relatives among cultured bacterial isolates. On the basis of phylogenetic data, this organism is considered to belong to a new genus, Defluvicoccus, represented by the species Defluvicoccus vanus sp. nov., a name chosen because of the distinctive staining properties of this organism; only the cell wall stained strongly with a wide range of stains, giving the cell a hollow and empty appearance. No intracellular polyphosphate granules could be detected after staining, but poly-beta-hydroxyalkanoate inclusions were detected using Nile blue A staining. Because of its taxonomic distance from its closest relatives among the 'Alphaproteobacteria', namely members of the genera Azospirillum, Phaeospirillum, Rhodospirillum, Rhodocista, Magnetospirillum and Rhodospira, D. vanus is considered to represent a new phylogenetic lineage within subgroup 1 of the 'Alphaproteobacteria', the D. vanus subgroup. The type strain is Ben 114(T) (=NCIMB 13612(T)=CIP 107350(T)).
Keywords: DNA bakterií; geny rRNA; DNA, Ribosomal; Phylogeny; Sewage; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Genes, rRNA; RNA ribozomální 16S; Phenotype; RNA, Ribosomal, 16S; sekvenční analýza DNA; DNA, Bacterial; odpadní vody; fylogeneze; fenotyp; Rhodospirillaceae; ribozomální DNA; Bacterial Typing Techniques; techniky typizace bakterií